Normal Saline Versus Betadine use to Reduce the Incidence of Wound Infection in Cesarean Section, A Cross Sectional Comparative Study - Asma Yasin, Samar Hussain, Mehvish Javeria, Saima Qurban, Muhammad Naim Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and Objectives: The aims and objectives of this study was to observed the difference between using betadine or normal saline irrigation of wound prior to skin closure in reducing the surgical site infections. Design of the Study: It’s a case-control study Study Settings: The study was conducted at Department of Obstetrics &Gynecology Rashid Latif Medical College, Lahore from June 2021 to November 2021. Material and Methods: For current study 200 pregnant women were selected and equally divided them into two different groups i.e. Group A and Group B. All individuals of Group A, used betadine liquid for surgical wound irrigation while the individuals of Group B, were used normal saline for such purpose. The observed raw data were statistically analyzed by SPSS 21, one –way ANOVA in which analysis of variance followed by mean standard deviation (Mean±SD) and P values (p<0.05) for significant. Results: The findings of current study indicated that wound irrigation with betadine liquid or normal saline have their own importance. The results are significant (p<0.05) in comparative analysis of Group A and Group B regarding allergy, postoperative wound cellulitis, postoperative wound abscess, postoperative fever and obstetric hemorrhages. Conclusion: The findings of current study indicated that Normal saline irrigation is better than betadine because of skin irritation and allergy due to iodine and toxicity of povadine iodine solution against healthy cells.